Correlation of in vitro and in vivo acetaminophen availability from albumin microaggregates oral modified release formulations - Torrado, G.; Carrascosa, C.; Torrado-Santiago, S. (International journal of pharmaceutics, 2001)
The aim of this study was to develop albumin microaggregated oral formulations for controlled drug release, and to reveal the possible influence of the release site on drug absorption. Acetaminophen was chosen as the model drug, which is included in the Class 1 group of the Biopharmaceutics Classification System (BCS). Albumin micro aggregates were formulated into tablets to obtain different drug release rates: Immediate Release (IR) tablets, multiparticulate systems with an intermediate release rate, and matrix systems showing slow release rate. The properties of the products were initially tested via dissolution studies, and then via bioavailability studies in healthy volunteers. Controlled release albumin microaggregated acetaminophen formulations for oral administration were obtained. The extent of drug absorption was comparable for all formulations, suggesting that the differences found in saliva concentration and urine cumulative profiles could be attributed merely to differences in drug release kinetics, as confirmed by the in vitro–in vivo correlation study. Therefore, it can be concluded that extended release of acetaminophen does not influence its absorption via intestinal heterogeneity.